Studies in Josephus and the varieties of ancient Judaism : Louis H. Feldman jubilee volume - Cohen, Shaye J. D.; Feldman, Louis H.; Schwartz, Joshua. (Ancient Judaism and Early Christianity, 2007)
Former students, colleagues and friends of the eminent classicist and historian Prof. Louis H. Feldman are pleased to honor him with a Jubilee volume. While Prof. Feldman has long been considered an outstanding scholar of Josephus, his scholarly interests and research interests pertain to almost all aspects of the ancient world and Jews. The articles in Judaism in the Ancient World: Louis H. Feldman Jubilee Volume relate to the fields studies by Prof. Feldman such as biblical interpretation, Judaism and Hellenism, Jews and Gentiles, Josephus, Jewish Literatures of the Second Temple, History of the Mishnah and Talmud periods, Jerusalem and much more. The contributors to this volume are among the most prominent in their fields and hail from the international scholarly community.